Factors influences the investors’ behavior trading in Bursa Malaysia at RHB Bank, Kuching / Julia Bujang - Bujang, Julia (2005)
This study was carried out to identify factors that influenced the investors’ behavior trading in Bursa Malaysia through RHB Bank, Simpang Tiga Branch in Kuching, Sarawak. A total of 150 respondents selected for this study consisted of the existing client investors of RHB Bank, investors randomly selected at share trading halls and the remisiers and dealer representatives from other Banks and stock broking firms. Telephone interviews were conducted with the existing RHB Bank’s investors while printed questionnaires were distributed to the investors and remisiers and dealer representatives of other institutions. Of the 150-targeted samples, 115 samples were received making up the primary data input. The investors were asked to answer 30 questions, which covered the respondents’ profiles, factors that influences their trading behavior and their most preferred counter. The study found out that investors were influenced by internal and external factors when trading in the stock market. Expected returns, personal confidence and risk preference were internal factors that were found to have largely influenced the investors’ trading behavior. External factors such as information, public listed company’s profile, family members, friends and remisiers or dealers were analyzed. The study found out that the most influential factor that influenced the investors was the advice received from the professionals such as the fund manager, remisiers and dealer representatives. The most preferred types of counters preferred by investors were strong counters or blue chips as well as speculative counters.